Mobile Learning Concepts for Older Adults: Results of a Pilot Study with Tablet Computers in France and Germany - Hetzner, Sonia; Leen-Thomele, Eline; Held, Paul (SPRINGER INTERNATIONAL PUBLISHING AG, GEWERBESTRASSE 11, CHAM, CH-6330, SWITZERLAND, 2016)
This paper sums up the evaluation results of a tablet computer course for older adults. As part of an European research project, the SenApp project, online course modules were developed to teach older adults the first steps on a tablet computer. After the course, a questionnaire was filled in Germany and France (N = 26). The evaluation focused on differences in satisfaction with support and course contents and in learning routines between age groups, education level, countries and pre-experience conditions. Main findings suggest that both courses were rated good, but that some support and content aspects were rated less good in France and by lower educated participants, by participants with less pre-experience in e-learning and by older age groups. This suggests that future course concepts should be created more flexible with different learning amounts for different experience levels and that especially support possibilities can be improved for some groups.
Keywords: Older adults; Tablet computer; ICT courses